Effects of the time of day on repeated all-out cycle performance and short-term recovery patterns - Giacomoni, M.; Billaut, F.; Falgairette, G. (International Journal of Sports Medicine, 2006)
The effect of the time of day on repeated cycle sprint performance and short-term recovery patterns was investigated in 12 active male subjects (23 ± 2 years, 76.4 ± 4.2 kg, 1.80 ± 0.06 m, 9.5 ± 4.5 h · week-1 of physical activity). Subjects performed ten 6-s maximal sprints inter-spaced by 30 s rest in the morning (08 : 00 - 10 : 00 h) and in the evening (17 : 00 - 19 : 00 h) on separate days. During the intermittent exercise, peak power output (PPO, watts), total mechanical work (W, kJ), peak pedalling rate (PPR, rev · min-1), and peak efficient torque (PTCK, Nm) were recorded. The values at the 1st, the 5th, and the 10th sprints were used as mechanical indices of fatigue occurrence. Intra-aural temperature and maximal voluntary contraction of knee extensors muscles (MVC) were measured before (pre), immediately after (post) the cycle bouts and following a 5-min passive recovery period (post5). The MVC indices were used to further confirm occurrence of neuromuscular fatigue and to assess short-term recovery patterns from all-out intermittent effort. During the MVC, electromyographic activity of the vastus lateralis muscle was recorded and analysed as its root mean square (RMS). The torque produced per unit RMS was calculated and used as index of neuromuscular efficiency (NME). A main effect for the sprint number was observed for all cycle performance parameters (p < 0.05). The main effect for the time of day was not significant for any biomechanical indices of neuromuscular performance. A significant interaction effect of the time of day and the sprint repetition was demonstrated on PTCK (F2,22 = 4.3, p < 0.05). The decrease in PTCK consecutive to sprint repetition was sharper in the evening compared to the morning (sprint 10 [% of sprint 1]: - 9.5 % in the evening vs. - 2.2 % in the morning, p < 0.05). Significant interaction effects of the time of day and the condition (i. e. pre, post, post5) were also demonstrated for RMS (F2,22 = 3.6, p < 0.05) and NME (F2,22 = 4.5, p < 0.05) during MVC. These interactions were characterised by similar patterns of fatigue occurrence (i. e. post vs. pre condition) in the morning (+ 7.5 % for RMS, - 19.6 % for NME) as in the evening (+ 10.2 % for RMS, - 19.4 % for NME) but different patterns of short-term recovery (i. e. post5 vs. post condition; p < 0.05) in the morning (- 7.3 % for RMS, + 13.7 % for NME) compared to the evening (+ 3.3 % for RMS, - 1.8 % for NME). These results suggest that short-term recovery patterns of neuromuscular function are slower in the evening compared to the morning.